Solve algebraically 6a + b = 16 & 5a - 2b = 19

6a + b = 16    Equation 1
5a - 2b = 19    Equation 2

Scale up one equation so both equations have same coeffient of one variable ie 2 times Equ 1

12a + 2b = 32
5a - 2b = 19

Add variables of each equation, hence eliminating variable b

17a = 51

Divide both sides by 17

a=3

Substitute a=3 into either one of the original equations

5(3) - 2b = 19

15 - 2b = 19

Subtract 15 from both sides of equation

-2b = 4

Divide both sides by -2

b = -2

Hence final answer: a=3, b=-2

Answered by Euan M. Maths tutor

2865 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

How do I factorise quadratic equations?


Work Out (2+11/15 )-(1+1/3)


prove that (3x+1)^2 - (3x-1)^2 is a multiple of 4 for all positive integer values of x


How would I find the formula for the nth term of a sequence such as 3, 7, 11, 15, 19?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences